High response and re‐infection rates among people who inject drugs treated for hepatitis C in a community needle and syringe programme. Issue 5 (12th December 2018) - Schulkind, Jasmine; Stephens, Brian; Ahmad, Farsana; Johnston, Linda; Hutchinson, Sharon; Thain, Donna; Ward, Zoe; Vickerman, Peter; Hickman, Matt; Dillon, John F.
Summary: To achieve WHO hepatitis C virus (HCV) elimination targets by 2030, mathematical models suggest there needs to be significant scale‐up of treatment among people who inject drugs (PWID). We tested whether people who actively inject drugs can be recruited and treated successfully through a community needle and syringe programme (NSP), and assessed rates of re‐infection. 105 HCV RNA positive participants were enrolled prospectively. Participants were recruited from the largest NSP in Dundee over 42 months. 94/105 individuals commenced treatment. Genotype 1 (G1) individuals (n = 37) were treated with peg‐interferon+ribavirin+Simepravir/Telaprevir. Genotype 2/3 (G2/3) (n = 57) received peg‐interferon+ribavirin. Weekly study visits took place within the NSP. Mean age of participants was 34.0 years (SD 6.9), 71.3% (61/94) were male. One in five (20/94) participants were homeless. 68.1% (64/94) were on OST (opiate substitution therapy) at enrolment; participants injected median 6.5 times/wk. In terms of clinical outcomes, >80% treatment adherence was 71.3% (67/94). There was no difference in SVR‐12 rates by genotype: 81.0% (30/37) for G1 and 82.5% (47/55) for G2/3. At 18 months post‐treatment, 15/77 participants were reinfected, followed up over 69.8 person‐years, yielding a re‐infection rate of 21.5/100 person‐years (95% CI 13.00‐35.65). This trial demonstrates that HCV treatment can be delivered successfully to the target population of treatment as prevention strategies. We report higher rates of re‐infection than existing estimates among PWID. Scale‐up of HCV treatment should be pursued alongside a comprehensive programme of harm reduction interventions to help minimize re‐infection and reduce HCV transmission.